Designing the Islamic Component of a Proposed World Religion Curriculum for South African State Schools - Ray Basson (International Institute of Islamic Thought, 1995)
An aspect of curriculum policy-making under the past Nationalist government had to do with policy being used to develop and impose the state’s nationalist and religious ideology-Christian National Educationon all schools in South Africa after its assumption of power in 1948. One consequence of this policy was that the rich diversity of South Africans as a people holding to multiple, positive, and idiosyncratic beliefs linked to various communal identities was sacrificed to a state-imposed pseudocommonality. Part of the challenge of educational reconstruction under the democratic government elected in April 1994 is to develop curricula that both recognize the diversity of positive ideals, beliefs, and faith while remaining impartial, if not agnostic,’ toward any one belief and to contribute to the development of a new and shared national identity. Following ministerial approval, an “Accommodation Model” for teaching religion has been announced recently. In it, schools are allowed to choose between teaching “one . . . faith” as an academic curriculum, a “world religion” curriculum, or a “combination” of the two, as religious education in the core curriculum and/or as an academic subject leading to certification. We suggest that the impetus for a world religion curriculum has to do with a desire to develop in all students an understanding of the diversity of faiths in the country and to move away from the solely Biblecentered programs of the past. In this article, we consider the design of the Islamic component for inclusion as one component in the proposed world religion curriculum. Its purposes are considered against the backdrop of ...